Nielsen’s Arcadia: The Case of the Flute Concerto - Ross, Ryan (Carl Nielsen Studies, 2012)
In this essay I suggest that there are distinct patterns pertaining to the Flute Concerto involving the idea of ‘Arcadia’ as it contrasts an idyllic past with a troubled present. In my analysis, I argue that his positioning of simple themes with relation to their surroundings in the concerto’s two movements suggests a process-driven search for an Arcadian ideal. As such, and far from simply being merely an interesting work with several beautiful moments, the concerto is an important access point both for further understanding Nielsen’s creative approach to form and his late-period preoccupation with the idea of simplicity.